Bilgi verme ve ibraz ödevi kapsamında vergi hukukunda susma hakkı - Akkan, Ali (My University, 2025)
Bilgi verme ve ibraz ödevi kapsamında vergi hukukunda susma hakkı Türk vergi sisteminde, beyan usulüne geçerlidir. Bu nedenle mükellef ile vergi idaresi arasında iş birliğinin bulunması ve mükellefin beyanlarının doğruluğunun denetlenmesi gerekmektedir. Bu kapsamda birçok ödevle yükümlendirilen mükelleflerin, bilgi verme ve defter ve belgeleri ibraz bu ödevlerden birisidir. Vergi idaresi, diğer ödevler ve imkânlar yanında, mükellefleri Vergi Usul Kanunu m. 148 uyarınca bilgi vermeye veya m. 256 uyarınca defter ve belgeleri ibraza mecbur tutabilmektedir. Bilgi verme ve ibraz ödevi, vergisel işlemlerin gerçek mahiyetinin belirlenmesi ve vergi suçlarının tespit edilmesine ilişkin bir ispat aracıdır. Bu nedenle kanun koyucu, defter ve belgeleri ibraz etmeyen mükellefler hakkında; Vergi Usul Kanun kapsamında ağır para ve hapis cezaları öngörmüştür. Ancak bilindiği üzere Anayasa m. 38/ 5’te, hiç kimsenin kendisi ve yakınları aleyhine delil sunmaya zorlanamayacağı ilkesi anayasal koruma altındadır. Bu kapsamda sunulan bilgi, belge ve defterlerde; mükellefin “kendisi aleyhine delil” olduğu takdirde bilgi verme ve ibraz ödevi ile susma hakkı çatışacaktır. Bu çalışma kapsamında; bilgi verme ve ibraz ödevi ile susma hakkı arasındaki sınır tayin edilmeye çalışılacaktır.

The right to silence in tax law within the scope of the duty to provide information and submit In the Turkish tax system, the declaration procedure is valid. For this reason, there must be cooperation between the taxpayer and the tax administration and the accuracy of the taxpayer's declarations must be checked. In this context, taxpayers are charged with many duties, and one of these duties is to provide information and submit books and documents. In addition to other duties and opportunities, the tax administration may oblige taxpayers to provide information pursuant to Article 148 of the Tax Procedure Law or to submit books and documents pursuant to Article 256. The duty to provide information and present is a means of proof for determining the true nature of tax transactions and detecting tax crimes. For this reason, the legislator has imposed heavy fines and imprisonment within the scope of the Tax Procedure Law for taxpayers who do not submit books and documents. However, as is known, the principle that no one can be forced to give evidence against herself or her relatives is constitutionally protected in Article 38/ 5 of the Constitution. In this context, if the information, documents and books presented constitute evidence against the taxpayer, the duty to provide information and present will conflict with the right to remain silent. Within the scope of this study, the boundary between the duty to provide information and presentation and the right to remain silent will be determined.
The right to silence in tax law within the scope of the duty to provide information and submit
Keywords: Adil Yargılanma Hakkı; Law and legislation; Mükellef Hakları; Right To A Fair Trial Taxpayer Rights; Right To Remain Silent; Susma Hakkı Tax Law; Taxation; Turkey; Türkiye; Vergi hukuku